(untitled) (Islamic Sciences Journal, 2024)
The importance of this study comes from the virtue and importance of the Sunnah of the Prophet, which is the second source of Islamic legislation, as knowledge of the condition of the men of the chain of transmission who lead to the narration of the Prophet – may Allah bless him and grant him peace - is one of the most important aspects of preserving this religion. Therefore, we see that critics from the people of this matter paid attention to the chain of transmission thorough investigation into the conditions of the narrators, examining and modifying them. According to the critics, mixing is considered one of the important matters for preserving the Sunnah of the Prophet, and it is worth noting to determine the period during which the narrator whose narration was accepted was mixed, as it is one of the most difficult tasks of critics, because mixing begins gradually, which affects the acceptance of the narration before it becomes clear and appears to the public. Objective of the study: The study aims to identify the methods and approaches followed by hadith scholars in explaining the condition of the mixed narrator to avoid the transmitted narrators being deceived by the mixed narration, especially the preserved ones. The reason for choosing the topic: The topic is chosen in order to show that the effect of mixing on the response of the novel is important. Some of the narrations are rejected and some are accepted, and this is what will become clear through my research. Research method and plan: I followed the research and inspection method in the books of al-Jarh and al-Ta’deel to investigate the mixed people who did not narrate after the mixing, whether it was from themselves, their families, or the narrators on their authority, then I studied their conditions and the critics’ sayings about them before the mixing